Kinetika Reaksi Curing Resin Epoksi Dengan Heksametilendiamin = Kinetics of Curing Reaction of Epoxy Resin with Hexamethylenediantine - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Curing reaction of diglycidyl ether of -bisphenol A (DGEBA) with hexamethylenediamine (HMDA) is an addition reaction, forming polymer with a three-dimensional networks structure. This research studied the effect of temperature and initial concentration ratio of HMDA:DGEBA upon the rate constants. There were two rate constants: the rate constant of linear reaction (IQ) and rate constant of branch reaction (k2). This research proposed two models: Ideal model ( based on Flory theory ) and Non-ideal model ( considered structure and molecular weight }. Experiment was carried out in a stirred batch reactor equipped with water bath. Sample was taken at certain time to determine the epoxy equivalent left. DGEBA of 60 g was used. The effect of temperature was investigated at concentration ratio of HMDA : DGEBA of 7 phr with temperature range of 30Â°C-50Â°C (5Â°C interval). The effect of concentration ratio HMDA:DGEBA was investigated at constant temperature of 40Â°C with concentration ratio range of 4 phr -16 phr ( 3 pill. interval ). It was concluded that the Non-ideal model was more appropriate for the curing reaction of DGEBA with HMDA than the Ideal model. Beside that, Non-ideal model could predict the molecular weight distribution. The effect of reaction temperature and initial concentration ratio HMDA : DGEBA upon the-rate constants could be expressed as : k = CAo 2.4551.105 (â `1731 i exp 4749.24 ) T ) CBÂ° ) k = ' 915 exp( 2.5149.1010 (âCA1 8374.75) T ) 2 C